Phenotypic Detection of ESBL-producing Escherichia coli from Faecal Samples of Stray Dogs in Kirtipur Municipality, Kathmandu, Nepal - Sharma, Supriya; Shrestha, Arju; Chaudhary, Amar; Thapa, Parisha; Sharma, Sulekha (Tribhuvan University Journal, 2026)
Extended-spectrum β-lactamase (ESBL) producing Escherichia coli represents an increasing public health concern due to its ability to inactivate third-generation cephalosporins and frequent association with multidrug resistance. Antimicrobial resistance has been widely investigated in clinical settings in Nepal, but limited information is available in stray animal populations. Stray dogs that are exposed to contaminated waste and sewage may serve as reservoirs of resistant bacteria and contribute to environmental dissemination. This cross-sectional study was conducted from June to December 2025 in Kirtipur Municipality, Kathmandu, to assess fecal carriage of ESBL-producing and multidrug-resistant (MDR) E. coli among stray dogs. Thirty fresh fecal samples were collected non-invasively and processed for culture using standard microbiological procedures. Isolates were identified by colony characteristics, Gram staining and biochemical tests. Antimicrobial susceptibility testing was done by the modified Kirby–Bauer disk diffusion method following CLSI 2024 guidelines, and ESBL production was confirmed phenotypically using the combination disk method. From the 30 samples, 52 morphologically distinct E. coli isolates were isolated. The dog-level carriage rate of phenotypically confirmed ESBL E.coli was 16.7% (5/30), and MDR was 23.3% (7/30). At the isolate level, 9.6% (5/52) were phenotypically confirmed as ESBL-producers and 13.5% (7/52) were MDR. The presence of antibiotic resistant E. coli in stray dogs indicates that these animals might contribute to the circulation of antimicrobial resistance in urban environments.